Theories Of Analyzing the Social and Psychological Effects of Drug - Rebin Kakamam Omer Bawzi; . Zana Ahmed Perdawd (QALAAI ZANIST SCIENTIFIC JOURNAL, 2023)
Summary This study highlights the analysis of the social and psychological effects of drug use, from the perspective of social and psychological theories, which consider drugs to be a terrible threat to the structure of individuals, families and society. This is a phenomenon that has spread around the world, and statistics have been serious. In the Kurdistan region, the trade in narcotics continues to increase, creating many psychological and social issue This study is an attempt to determine the extent to which the social and psychological effects.